2017
DOI: 10.4172/pharmaceutical-sciences.1000198
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Weight Control Counseling in Overweight and Obese Young Adults

Abstract: Phimarn, et al.: Weight Control Counselling in Young AdultsThis study was carried out to compare groups with individual counselling to examine essential outcomes in young adults in a community pharmacy. A randomized controlled trial was conducted from June 2011 to February 2012. A total of 112 overweight and obese participants were randomly assigned to receive group counselling (n=52) or individual counselling (n=56). Clinical outcomes included weight, waist circumference and body mass index. Eating behaviours… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…Two studies involved interventions focused on nutrition, PA and weight delivered in different face-to-face session formats [ 83 , 90 ]. Hivert et al reported greater changes in weight (− 1.3 kg, p = 0.04) and BMI (− 0.5 kg/m2, p = 0.01) for participants in the group session intervention compared with no intervention at the end of the 2-year intervention [ 83 ], while Phimarn et al reported greater weight loss (− 1 kg, p = 0.04) for participants in the individual session intervention compared with group sessions at the end of the 6-month intervention [ 90 ]. LaRose et al compared interventions targeting large changes/larger initial weight loss versus small changes/gradual weight loss, with greater weight loss achieved in the large changes group at 2 years (− 2 kg, p = 0.006) [ 84 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Two studies involved interventions focused on nutrition, PA and weight delivered in different face-to-face session formats [ 83 , 90 ]. Hivert et al reported greater changes in weight (− 1.3 kg, p = 0.04) and BMI (− 0.5 kg/m2, p = 0.01) for participants in the group session intervention compared with no intervention at the end of the 2-year intervention [ 83 ], while Phimarn et al reported greater weight loss (− 1 kg, p = 0.04) for participants in the individual session intervention compared with group sessions at the end of the 6-month intervention [ 90 ]. LaRose et al compared interventions targeting large changes/larger initial weight loss versus small changes/gradual weight loss, with greater weight loss achieved in the large changes group at 2 years (− 2 kg, p = 0.006) [ 84 ].…”
Section: Resultsmentioning
confidence: 99%
“…Of the 22 gender-neutral studies, 13 were effective (59%), most of which were for absolute weight (n = 10, 59%). Six of nine weight gain prevention studies (67%) [82][83][84][85][86][87] and seven of 13 weight loss studies (54%) [88][89][90][91][92][93][94] were effective. Bertz et al found that daily self-weighing with feedback achieved greater weight loss than irregular self-weighing without feedback over a one year intervention period (− 1.6 kg, p = 0.04) [82].…”
Section: Obesity Outcomes Outcome Effectiveness: Narrative Summarymentioning
confidence: 99%
See 1 more Smart Citation
“…Our results suggest that although participants who were overweight/obese had a slightly higher attitude in using food apps, adolescents with normal/underweight BMI had slightly higher SN, PBC and behavioural intentions; however, this did not yield significance (p > 0.05). In a study conducted in Thailand among 112 overweight (n = 52) and obese (n = 56) young adults, the overall mean TBP score increased significantly from baseline in the health dieting behaviour and SN following group counselling, concluding that group counselling was not inferior to individual counselling and that group counselling is a better option for healthy dieting management [45]. In Greece, between the normalweight group and overweight/obese group, correlations between variables of TPB and behaviours (healthy eating and exercise) were higher in the normal-weight group than in the overweight/obese group, whereas attitude was a significant predictor for those with higher values in the normal-weight group [46].…”
Section: Discussionmentioning
confidence: 97%
“…However, the effectiveness of this counseling method needs to be investigated further. In some studies, on obese patients, group counseling produced significantly greater reduction in weight than individual therapy did [26][27][28][29], and it was recommended as a first-line approach for weight management in young adults [30]. It is, nonetheless, possible that in our study, individual education had a greater impact on individual behavior because it is personalized to a patient's needs and the dietitian-patient relationship is greater than the one in a group education method.…”
Section: Discussionmentioning
confidence: 99%